Risky eating behaviour and physical self-concept in nurse students in Huanuco - Huapalla Céspedes, Bethsy Diana (2019)
Objective. To determine the relationship between risky eating behaviour and physical self-concept that Hermilio Valdizan university nurse students have, in Huánuco by 2018. Methods. An observational, prospective and analytical study was conducted. a socio-demographic background questionnaire was applied. the brief risky eating behaviour and physical self-concept questionnaire, to 141 nurse students, through probabilistic sampling by quotas. cramer’s v was used for the hypothesis check based on the pearson’s chi-squared test value, with a probability of significance of 0.05. Results. It was shown that the highest proportion of students are between the ages of 18 and 22, belonging to the female gender and single. 37.6 % live in  Huánuco, 53.2 % live with their parents, 65.2 % are catholic, 79.4 % only study and 66 % consume their food at home. 14.2 % have risky eating behaviour and about the physical self-concept, 79.4 % show an average level of positive perception. there is a relationship between risky eating behaviours and the level of physical self-concept in the dimensions: physical condition,  general physical self-concept, general self-concept (weak association) and physical attractiveness (moderate association). not being related to the dimensions: physical ability and strength. Conclusion. There is a relationship between risky eating behaviours and physical self-concept (x2 : 14,627 an a p= 0.001), with a moderate level of association (cramer’s v = 0.322)